2006
DOI: 10.1016/j.yexcr.2006.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel Dp71 dystrophin-associated protein complex (DAPC) present in the nucleus of HeLa cells: Members of the nuclear DAPC associate with the nuclear matrix

Abstract: , et al.. Characterization of a novel Dp71 dystrophin-associated protein complex (DAPC) present in the nucleus of HeLa cells: members of the nuclear DAPC associate with the nuclear matrix.. Experimental Cell Research, Elsevier, 2006, 312 (16) ABSTRACT: Dystrophin is an essential component in the assembly and maintenance of the dystrophinassociated protein complex (DAPC), which includes members of the dystroglycan, syntrophin, sarcoglycan and dystrobrevin protein families. Distinctive complexes have been descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 49 publications
6
59
0
Order By: Relevance
“…The presence of β-sarcoglycan in nuclei was previously reported in HeLa cells based on confocal microscopy and also its association with the nuclear matrix. Similar observations have also been made for Dp71 dystrophin, β-dystroglycan, α-and β-syntrophin, α1-and β-dystrobrevin (Fuentes-Mera et al, 2006). Moreover, Dp71 dystrophin is also localized in the nuclei of PC12 cells (Calderilla-Barbosa et al, 2006).…”
Section: Sub-cellular Distribution Of Dscgβ During the Cell Cyclesupporting
confidence: 83%
See 1 more Smart Citation
“…The presence of β-sarcoglycan in nuclei was previously reported in HeLa cells based on confocal microscopy and also its association with the nuclear matrix. Similar observations have also been made for Dp71 dystrophin, β-dystroglycan, α-and β-syntrophin, α1-and β-dystrobrevin (Fuentes-Mera et al, 2006). Moreover, Dp71 dystrophin is also localized in the nuclei of PC12 cells (Calderilla-Barbosa et al, 2006).…”
Section: Sub-cellular Distribution Of Dscgβ During the Cell Cyclesupporting
confidence: 83%
“…On the other hand, several recent studies have revealed that mammalian DGC components are also present in cytoplasm and nuclei (Calderilla-Barbosa et al, 2006;Fuentes-Mera et al, 2006;Marquez et al, 2003;Radojevic et al, 2000). However, no study which addresses their dynamics of distribution on cell cycle progression has been reported so far.…”
Section: Sub-cellular Distribution Of Dscgβ During the Cell Cyclementioning
confidence: 99%
“…Although dystrobrevin, at first considered a cytoplasmic component of the DPC, has already been described in the nuclear compartment (37,41), iBRAF was so far regarded essentially as a nuclear protein (35). Our confocal microscopy results show that iBRAF and ␤-dystrobrevin colocalize in the nucleus as well as in the cytoplasm of co-transfected cells.…”
Section: Discussionmentioning
confidence: 46%
“…However, ␣-Syntrophin and Dystrophin have been also observed in the inner nuclear membrane of cultured myocytes, and its level increases during myogenesis in nuclei (57,58). Interestingly, nNOS␣ has been revealed in the nuclear membrane of HeLa cells in association with Dystrophin and ␣-Syntrophin (46). We have demonstrated that nNOS was no more able to be translocated in the nucleus when ␣-Syntrophin was down-regulated.…”
Section: Discussionmentioning
confidence: 69%
“…␣-Syntrophin Is Implicated in nNOS Recruitment to Nuclei-␣-Syntrophin, which is a known interactor of nNOS at the sarcolemma (6), was found in the nuclear compartment of HeLa cells, and at this level it is part of the nuclear Dystrophin complex together with nNOS (46). Interestingly, ␣-Syntrophin was also localized in nuclei of C2C12 cells (55).…”
Section: -E) Nuclear Recruitment Of Nnos Promotes Pgc-1␣ Expression mentioning
confidence: 99%